2004
DOI: 10.1021/jo048418t
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Self-Decomposition and Hydrogen Atom Transfer Reactions of Substituted Phthalimide N-Oxyl Radicals in Acetic Acid

Abstract: Kinetic data have been obtained for three distinct types of reactions of phthalimide N-oxyl radicals (PINO(.)) and N-hydroxyphthalimide (NHPI) derivatives. The first is the self-decomposition of PINO(.) which was found to follow second-order kinetics. In the self-decomposition of 4-methyl-N-hydroxyphthalimide (4-Me-NHPI), H-atom abstraction competes with self-decomposition in the presence of excess 4-Me-NHPI. The second set of reactions studied is hydrogen atom transfer from NHPI to PINO(.), e.g., PINO(.) + 4-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
73
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(83 citation statements)
references
References 20 publications
(41 reference statements)
9
73
0
1
Order By: Relevance
“…[9,14,15,17,18,25] The contribution from tunnelling is clear, as also documented elsewhere. [14,17] c -Products study for reaction of TFNO with a probe substrate.…”
Section: Scheme 3 Competition Of Et Vs Hat Routes With An Aminoxyl Rsupporting
confidence: 64%
See 2 more Smart Citations
“…[9,14,15,17,18,25] The contribution from tunnelling is clear, as also documented elsewhere. [14,17] c -Products study for reaction of TFNO with a probe substrate.…”
Section: Scheme 3 Competition Of Et Vs Hat Routes With An Aminoxyl Rsupporting
confidence: 64%
“…[14,16,17] Summing it up, the reactivity features of TFNO in the HAT process (Table 2) are akin to those of other aminoxyl radicals, [10] including the finding of an accelerating effect from electron-donor and the retarding effect from electron-withdrawing substituents on the benzylic substrate. Significant figures for this comparison of reactivity among aminoxyl radicals are selected and given in Table 3, proper allowance being made to the different solvents employed (no major effects upon the rates are however expected in these radical processes [14,15,25] ).…”
Section: Characterization Of the Radical Tfnomentioning
confidence: 99%
See 1 more Smart Citation
“…However, Espenson and co-workers, have recently reported [26] that the rate constants for hydrogen atom abstraction by PINO from p-xylene and toluene using NHPI/Co III were "slightly different" from those obtained using NHPI/Pb(OAc) 4 .…”
Section: Resultsmentioning
confidence: 93%
“…Chester et al [68] found that the optimum Co/Zr ratio in neat acetic acid was 6-7 for maximum TPA yield and minimum induction period. Promotors such as CoBr 2 -MnBr 2 [69,70] instead of HBr as a bromine source, N-hydroxyphthalimide [71,72], and N-hydroxy succinimide [73,74] have also been reported for pX oxidation to TPA under milder conditions (~100 °C), but the pX conversion and TPA selectivity are below the typical industrial values.…”
Section: Alternative Catalystmentioning
confidence: 99%